Increase of fucosylated alpha‐fetoprotein fraction at the onset of autoimmune hepatitis and acute liver failure. Issue 14 (25th March 2014) - Yamagiwa, Satoshi; Tamura, Yasushi; Takamura, Masaaki; Genda, Takuya; Ichida, Takafumi; Ishikawa, Toru; Kamimura, Tomoteru; Takahashi, Toru; Suda, Takeshi; Matsuda, Yasunobu; Nomoto, Minoru; Aoyagi, Yutaka
<x xml:space="preserve">Abstract</x> Aim Increased serum α‐fetoprotein (AFP) has been associated with a good prognosis following acute liver failure (ALF), but the levels of the fucosylated fraction of AFP (Lens culinaris agglutinin‐reactive fraction of AFP [AFP‐L3]) following acute liver injury remain unknown. The aim of the present study was to investigate the clinical significance of AFP and AFP‐L3 in patients with acute liver injury. Methods We investigated the serum levels of AFP and highly sensitive AFP‐L3% in 27 patients with acute‐onset autoimmune hepatitis (AIH), 28 patients with acute hepatitis (AH) and 22 patients with ALF at the onset using a highly sensitive immunoassay (micro‐total analysis system). Results The serum AFP levels were increased in patients with AIH, AH and ALF, but the levels did not significantly differ among them. However, the mean AFP‐L3% level was significantly higher in patients with AIH than in patients with AH (P = 0.0039). Moreover, significantly more patients with AIH demonstrated AFP‐L3 positivity (≥10%) when compared with patients with AH (P = 0.014). Although the percentage of AFP‐L3 positivity increased with AFP levels, at low serum AFP levels (<10 ng/mL), significantly more patients with AIH demonstrated AFP‐L3 positivity than did patients with AH (P = 0.024) or ALF (P = 0.038). Conclusion We demonstrated for the first time that highly sensitive AFP‐L3% levels were increased at the onset of AIH. The mechanism underlying the increase in AFP‐L3 remains to be elucidated, but this finding may reflect an alteration of the glycosylation such as hyperfucosylation, which can influence the modifications of self‐antigens in hepatocytes.